2018
DOI: 10.1176/appi.ps.201700536
|View full text |Cite
|
Sign up to set email alerts
|

Use of Academic Detailing With Audit and Feedback to Improve Antipsychotic Pharmacotherapy

Abstract: Polypharmacy decreased among young and older adults after academic detailing with audit and feedback. Although further research is needed, this low-intensity intervention may help mental health systems reduce antipsychotic polypharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A study by Mary Brunette et al showed that providing clinical staff with educational courses and audits, combined with feedback on the accuracy of prescribed medications, reduced the phenomenon of polypharmacotherapy in psychiatry. According to the authors of the study, thanks to these practices, the phenomenon of antipsychotic polypharmacotherapy decreased from 13.1% to 10.9% [26]. Another study showed that patient-directed education is a very important tool in reducing excessive polypharmacotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…A study by Mary Brunette et al showed that providing clinical staff with educational courses and audits, combined with feedback on the accuracy of prescribed medications, reduced the phenomenon of polypharmacotherapy in psychiatry. According to the authors of the study, thanks to these practices, the phenomenon of antipsychotic polypharmacotherapy decreased from 13.1% to 10.9% [26]. Another study showed that patient-directed education is a very important tool in reducing excessive polypharmacotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…In a case note review of 154 cases, Unwin and Deb (2008) also reported poor documentation related to capacity issues and acquisition of consent. Periodic audit of antipsychotic prescribing practice has been advocated to be a valuable tool for promoting best practices for the use of antipsychotics (Adesola et al , 2013; Botvinik et al , 2004; Brunette et al , 2018; Fernando et al , 1997; Haw et al , 2008; Marshall, 2004; McMillan et al , 2017; Mortimer et al , 2005; Patel et al , 2014; Paton et al , 2016; Wheeler et al , 2009; Wightman et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…An audit from Nigeria revealed that high dose prescribing was common among inpatients (Adesola et al , 2013). Several other studies have also identified the importance of auditing antipsychotic prescribing (Botvinik et al , 2004; Brunette et al , 2018; Hassiotis et al , 2018; Haw et al , 2008; Lennox et al , 2007; Lunsky et al , 2007; Mortimer et al , 2005; Olashore et al , 2017; Patel et al , 2014; Wightman et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also found that report cards can improve medication management associated with antipsychotic prescribing. For example, one study demonstrated a reduction in antipsychotic polypharmacy in community mental health centers and a second study found an increase in metabolic monitoring in a large outpatient clinic [24,25]. Of note, a third study found no impact of report cards on high-dose antipsychotic prescribing or polypharmacy [26].…”
Section: Introductionmentioning
confidence: 99%